Molecular Aspects of Hematologic Malignancies Diagnostic Tools and Clinical Applications - Witt, Michal.; Witt, Michal.; Dawidowska, Malgorzata.; Dawidowska, Malgorzata.; Szczepanski, Tomasz.; Szczepanski, Tomasz. (Principles and Practice,, 2012)
This book provides a state-of-the-art approach to the molecular basis of hematologic diseases and its translation into improved diagnostics and novel therapeutic strategies. Several representative hemato-oncologic malignancies are analyzed in detail: acute lymphoblastic leukemia, acute myeloid leukemia, B-cell Non-Hodgkin lymphomas, multiple myeloma, chronic lymphocytic leukemia, chronic myeloid leukemia, myelodysplastic syndromes, and myeloproliferative neoplasms. Experts in the field describe the molecular methods applied for modern diagnostics and therapies, such as hematopoietic stem cell transplantation, donor recipient matching, banking of biological material, analyses of post-transplant chimerism, and minimal residual disease monitoring. The volume concludes with an extensive section comprising thorough step-by-step protocols of molecular techniques in hematology, all of them validated in the authors’ own laboratories. !